Upaya Pemberdayaan Masyarakat dalam Pencegahan dan Perawatan Mandiri Penyakit Covid-19 - Ida Rosdiana; Yanti Cahyati; Yudi Triguna (Yayasan Inspirasi El Burhani, 2022)
Introduction: The rapid spread of the coronavirus has caused a Covid-19 pandemic worldwide. Like other countries in the world, Indonesia is still trying to prevent and handle Covid-19. However, proactive and independent actions can prevent this Covid-19 disease from the community. Hence, people need to increase their awareness in various efforts to prevent the occurrence of the Covid-19 disease. Objective: This community service activity aims to increase the community's independence in carrying out prevention and self-care efforts for COVID-19. The target to be achieved is that health cadres and the community have the knowledge and skills to prevent COVID-19 disease and can provide initial treatment in emergency cases in the community. Method: The method used is conducting cadre training, making educational media and providing education to the community. During training, cadres were given pre-test questions at the beginning of the meeting and post-test at the end of the meeting as an evaluation of the activities carried out. Result: The result of this activity is an increase in the knowledge and skills of cadres and the community, as evidenced by the increase in post-test scores during cadre training and the dissemination of information about the COVID-19 disease to the public well as the availability of educational media. Conclusion: This community service activity can increase the knowledge and independence of the community in making efforts to prevent and independently treat the Covid-19 disease, as well as handling emergencies that occur at home.